The efficacy of injection sclerotheraphy, fibrin glue and hemoclips in stopping bleeding from gastroduodenal ulcers - Pulanić, Roland; Brkić, Tomislav; Opačić, Milorad Krznarić, Željko; Rustemović, Nadan Jokić-Begić, Nataša; Ostojić, Rajko Vucelić, Boris (1998)
In this prospective study our team compared the three hemostatic procedures of the gastroduodenal bleeding ulcers: sclerotheraphy, hemoclips and fibrin glue. All three methods were equally effective in definitive hemostasis. Fibrin glue can be used as an elective method without concomitant tissue damages.
Projekt MZOS
ENG